RESPONSIBILITY OF THE STATE IN SOLVING CONFLICT AMONG RELIGIOUS PEOPLE (RESEARCH CONDUCTED IN CENTRAL JAVA - Rini Fidiyani (Jurnal Dinamika Hukum, 2016)
Freedom of choosing/believing religion/credo is a right guaranteed by the state (Article 28 E point (2) UUD 1945). Nonetheless, that freedom has become a mere myth since the state involves in violation against the freedom of religion/credo towards the minorities in solving their conflict in several places, particularly in Central Java. This research investigates the responsibility of the state towards that conflict using normative and empiric law approach as problem-solving methods. The result of this research  shows several things. First, there found unfairness in the state in solving conflict amongst religious people; Second, there found an involvement from certain religion follower (which supported by the state servant) in conflict amongst  religious people and in other violation against the freedom of religion; Third, it has not been unclear the acts of responsibilty from the state about their behaviours; and Fourth, there found no any way for the victims towards state’s behavior, to claim their rights. To solve the problem, it needs to be arranged in a normative or politic way about how the state takes responsible in dealing with conflict amongst religious people, either as a mediator or as the perpretator of discrimination or the offender of freedom of religion. Besides, we need also to find some ways for the victim to defend their rights and their freedom.Key words: freedom of religion, conflict, discrimination, responsibility of the state.